On the trend and variability of 18th century British Transatlantic slave prices - Joshy Easawa; Atanu Ghoshray (Cardiff University, Cardiff Business School, 2023)
The purpose of this shorter paper is to estimate the trend of 18 th century British slave prices. We apply robust econometric procedures on slave price data constructed by Whatley (2018) over the period 1699 to 1807 and find evidence of a structural break in 1740, thereby advocating a broken trend. We estimate the trend over two regimes demarcated by the structural break, concluding there is no significant trend in the first regime prior to 1740. However, in the second regime, slave prices show a significant positive trend increasing annually at around 2.4%. Since 1740, the slave prices are close to constant variance, lending support to the tighter confidence intervals that we obtain in the second regime. We document various accounts by historians that can help explain this steady increase, focusing on supply and demand side arguments.
Keywords: 330; Transatlantic slave trade; Slave prices; Structural breaks; trends; Britain; Africa